Impact of periodic current pulses on Li-ion batteries lifetime in vehicular application. (2015) - Savoye, FranÁ§ois; Venet, Pascal; Pelissier, Serge; Millet, Michael; Groot, Jens
Using the hybrid electric vehicle application as a reference, the possible impact of periodic current pulses on lithium ion secondary battery cycle life was evaluated. Several profile types, with and without pulses, were evaluated in a comparative study on cycle life of commercial graphite/LiFePO4 batteries. Results are presented, compared and analysed. Contrary to the well-known results on lead-acid batteries and to results in previously published work, there is no indication that periodic pulses could enhance the cycle life of Li-ion batteries. On the contrary, certain pulse patterns have been identified to be detrimental to Li-ion batteries.